Geochemical and Mineralogical Insights into Hydrothermal Alteration in the Beruang Kanan Non-Vulcanic Area, Central Kalimantan, Indonesia - Retno Anjarwati; Sutarto Sutarto; Dwi Fitri Yudiantoro; Arifudin Idrus; Emi Prasetyawati Umar (International Journal of Hydrological and Environmental for Sustainability, 2025)
Previous studies have revealed significant hydrothermal alterations within the Beruang Kanan Non-Volcanic Area, Central Kalimantan, Indonesia, resulting in extensive ore mineralizations. This study aims to examine the effects of hydrothermal processes on rock alteration, delineate alteration zones, and establish their relationship to metal mineralization. The research area, situated in the Tumbang Miri district of Gunung Mas regency, forms part of the Corrugated Hills Geomorphological Unit and is traversed by the Schwaner Mountains, with elevations ranging from approximately 50 to 400 meters. Stratigraphic analysis identifies three primary rock units, ordered from oldest to youngest: the Tuffaceous Sandstone Unit, the Dacitic Tuff Unit, and the Andesite Unit. Hydrothermal alterations have resulted in three distinct alteration zones sericitic, argillic, and propylitic characterized by secondary mineral assemblages. This study provides a comprehensive framework for understanding the geological and mineralization dynamics of non-volcanic hydrothermal systems in Central Kalimantan, Indonesia